2020
DOI: 10.1002/mbo3.1028
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Planococcus antioxidans sp. nov., an antioxidant‐producing strain isolated from the desert soil in the Qinghai–Tibetan Plateau

Abstract: Strain Y74T was an isolate from the sandy soil in the town of Huatugou, Qinghai–Tibet Plateau, China. An analysis of this strain's phenotypic, chemotaxonomic, and genomic characteristics established the relationship of the isolate with the genus Planococcus. Strain Y74T was able to grow between 4 and 42°C (with an optimum temperature of 28°C) at pH values of 6–8.5 and in 0%–7% (w/v) NaCl. The dominant quinones were MK‐8 and MK‐7. The polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Genomic DNA extraction was performed as described previously [19]. The full-length 16S rRNA gene sequence was extracted from the genome annotated in the NCBI Prokaryotic Genome Annotation Pipeline (PGAP) [20][21][22] and deposited as MZ497413.1 in the GenBank/EMBL/DDBJ databases.…”
Section: Phylogenetic Analysis Based On 16s Rrna Genesmentioning
confidence: 99%
“…Genomic DNA extraction was performed as described previously [19]. The full-length 16S rRNA gene sequence was extracted from the genome annotated in the NCBI Prokaryotic Genome Annotation Pipeline (PGAP) [20][21][22] and deposited as MZ497413.1 in the GenBank/EMBL/DDBJ databases.…”
Section: Phylogenetic Analysis Based On 16s Rrna Genesmentioning
confidence: 99%
“…We compared the 16S rRNA gene sequence of strain Y40 T with those of type strains in the EzTaxon database [16] ( Mesobacillus zeae JJ-247 T , Mesobacillus foraminis CV53 T , Mesobacillus maritimus KS16-9 T , Neobacillus soli NBRC 102451 T , Cytobacillus gottheilii WCC 4585 T and Neobacillus vireti LMG 21834 T ) and the similarities were 98.0, 97.7, 97.4, 97.1, 97.1 and 97.1 %, respectively. The highly related 16S rRNA gene sequences of the type strains from the genera Nesobacillus , Peribacillus , Neobacillus , Cytobacillus and Bacillus were chosen for phylogenetic analysis, along with Bacillus subtilis DSM10 T which was used as an outgroup.…”
Section: Phylogeny Based On the 16s Rrna Gene And Ubcg Setmentioning
confidence: 99%
“…The Qaidam Basin is located in the northeast Qinghai-Tibet Plateau, which is a very harsh environment with an arid climate and high solar radiation. These special characteristics have resulted in a large number of new untapped microbial resources in the region [14][15][16].…”
mentioning
confidence: 99%
“…These changes indicated that genus Planococcus and Planomicrobium have a close phylogenetic relationship. Usually, the main splitting points of the 16S rRNA sequence between the genera Planococcus and Planomicrobium were located at sites 183 and 190 ( E. coli counting), which in the Planococcus are T and A, whereas in the Planomicrobium are C and G [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Planococcus has the following known features: Gram-positive, multicellular morphology (cocci, short rod, or rod), aerobic, and no sporulation [ 8 ]. Representative strains of genus Planococcus usually grow in cold and/or saline-alkali soil with high salt concentrations, e.g., Arctic, Antarctic, and marine environments [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%